The Causes of Hypertension in Human Population visiting Sughra Shafih Medical Complex - Iqbal, Muhammad Naeem; Ashraf, Asfa; Shahzad, Mirza Imran; Alam, Saman; Xiao, Shiwei; Toor, Sabeen (PSM Biological Research, 2016)
The data about the major causes of hypertension of approximately one hundred patients of hypertension was collected by interviewing them at Sughra Shafih Medical Complex, Narowal. The data had been analyzed to determine the relative occurrence and incidence of hypertension and effects of various causes. The analysis shows that hypertensive patients were more prevalent (60%, n=60/100), and non-hypertensive patients were less prevalent (40%, n=40/100). The prevalence of hypertension was more in females (64.00%) as compared to males (34.00%). The major risk factors of hypertension were diabetes, obesity and overweight, tension, smoking. Some females were hypertensive during pregnancy. High cholesterol level also contributes to hypertension. In our sample out of hypertensive patients 42% were diabetic, 25% were obese, 10% were smokers, 16.6% were hypertensive because to tension and 7% females were hypertensive during pregnancy. It may persist for prolonged periods in the individual without signs well-known as â€œthe silent killerâ€, and may perhaps noticeable just after causing severe irretrievable pathology and complications.